Men’s Experiences of the Criminal Justice System Following Female Perpetrated Intimate Partner Violence - McCarrick, J.; Davis-McCabe, Catriona; Hirst-Winthrop, S. (2015)
© 2015 Springer Science+Business Media New York The current study aimed to explore men’s experience of the UK Criminal Justice System (CJS) following female-perpetrated intimate partner violence (IPV). Unstructured face-to-face and Skype interviews were conducted with six men aged between 40–65 years. Interviews were transcribed and analysed using interpretative phenomenological analysis (IPA). Due to the method of analysis and the sensitive nature of the research, the researcher engaged in a process of reflexivity. Four main themes were identified, including ‘Guilty until Proven Innocent: Victim Cast as Perpetrator;’ ‘Masculine Identity;’ ‘Psychological Impact’ and ‘Light at the End of the Tunnel.’ Themes were discussed and illustrated with direct quotes drawn from the transcripts. Directions for future research, criminal justice interventions, and therapeutic interventions were discussed.